A Review of 30 Tumours Affecting Joints - Whitelock, R. G.; Dyce, J.; Houlton, J. E. F.; Jefferies, A. R. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
The records and radiographs of 30 dogs with histopathologically confirmed tumours affecting joints were reviewed. The previously most commonly reported primary joint tumour, the synovial sarcoma, only represented eight of the 30 cases (27%). However, the radiological appearance of this tumour was very similar to others such as the fibrosarcoma, rhabdomyosarcoma, fibromyxosarcoma, malignant fibrous histiocytoma, liposarcoma and undifferentiated sarcoma. Other tumours recorded were a mast cell tumour, haemangiopericytoma, osteosarcoma, squamous cell carcinoma and amelanotic melanoma.This study shows that there are joint tumours that have a similar radiographic appearance to synovial sarcomata, and confirms the importance of histopathological diagnosis.This study shows that there are a number of different joint tumours which radiologically resemble synovial sarcoma, and underlines the importance of accurate histopathological diagnosis.
Keywords: Joint; tumour; radiology; dog